A study on the differences of financial variables between interest-free banks and conventional banks / Nur Baizura Zawawi - Zawawi, Nur Baizura (2007)
The aim of this study is to determine the structural differences between Islamic banking and conventional banks from Malaysia's perspectives. The study will further analyze the financial dimension which evaluate the performance of both banks namely the liquidity, leverage, profitability and efficiency by using the indicator of each financial variables. The data used in this study is derived from two Islamic bank and eight conventional banks in Malaysia. The financial ratios are used to evaluate the structural differences between the Islamic and conventional banks which are derived from the financial reports of these banks. The study uses the Islamic Banks and conventional banks as dependent variables and the financial ratios such as cash to total deposit, equity capital plus reserve to total asset, gross income before tax to total asset and operating expenses to total asset are used as independent variables and the indicator for the liquidity, leverage, profitability and efficiency. This study uses logistic regression approach to test the differences between the financial variables of both banks with different mode of operations whether their performance are the same or not. The result of the study shows that interest free banks and conventional banks are different in terms of their leverage and profitability variables but not in term of their liquidity and efficiency. This is due to their modes of financing which is different from each other. Interest-free bank more focus on Mudharabah and Musyarakah while conventional is more on loan and advance modes of financing investment.